From methods and concepts to triple learning processes in school, teacher education and research - Tjernberg, Catharina; Mattson, Eva Heimdahl (Nordic studies in education, 2017)
This article examines and discusses how successful teachers develop professionally and relate this process to theory and practice. It elucidates some further aspects of an earlier longitudinal, praxis-oriented study in excellence that was carried out over a period of seven years in a nine-year Swedish compulsory school (Tjernberg, 2013). That case study was based on classroom observations and follow-up discussions to create consciousness of learning processes among the teachers and the researcher. According to the teachers in this study, the focus of pedagogical research is seldom on pedagogical practices, which means that they are not felt to be important. In contrast, the research is seen to be important if it has an inside perspective, using mutual and continuous communication between the pupils, themselves, and the researcher. One main finding is that a researcher can contribute to theorising and putting into words the teachers' pedagogical practices. At the same time, the researcher is able to deepen her or his research into issues that arise from the teachers' practices and knowledge. These two conditions are in turn necessary for the individual pupil to develop her or his proximal learning, which leads to further research questions. In this article, the term 'triple learning process' is used to describe this interaction.